Non-thermal emission resulting from a supernova explosion inside an extragalactic jet - Vieyro, Florencia Laura (2019)
Context. Core-collapse supernovae are found in galaxies with ongoing star-formation. In a starburst galaxy hosting an active galactic nucleus with a relativistic jet, supernovae can take place inside the jet. The collision of the supernova ejecta with the jet flow is expected to lead to the formation of an interaction region, in which particles can be accelerated and produce high-energy emission. Aims. We study the non-thermal radiation produced by electrons accelerated as a result of a supernova explosion inside the jet of an active galactic nucleus within a star-forming galaxy. Methods. We first analyzed the dynamical evolution of the supernova ejecta impacted by the jet. Then, we explored the parameter space using simple prescriptions for the observed gamma-ray lightcurve. Finally, the synchrotron and the inverse Compton spectral energy distributions for two types of sources, a radio galaxy and a powerful blazar, are computed. Results. For a radio galaxy, the interaction between a supernova and a jet of power ∼10 43 -10 44 erg s -1 can produce apparent gamma-ray luminosities of ∼10 42 -10 43 erg s -1 , with an event duty cycle of supernova remnant interacting with the jet close to one for one galaxy. For a blazar with a powerful jet of ∼10 46 erg s -1 , the jet-supernova ejecta interaction could produce apparent gamma-ray luminosities of ∼10 43 -10 44 erg s -1 , but with a much lower duty cycle. Conclusions. The interaction of supernovae with misaligned jets of moderate power can be relatively frequent, and can result in steady gamma-ray emission potentially detectable for sources in the local universe. For powerful blazars much farther away, the emission would be steady as well, and it might be detectable under very efficient acceleration, but the events would be rather infrequent.